Nutritional, physicochemical, textural and sensory characterization of horsemeat patties as affected by whole germinated green buckwheat and its flour - Zhibek Atambayeva; Almagul Nurgazezova; Zhanna Assirzhanova; Zhumatay Urazbayev; Aray Kambarova; Assel Dautova; Berik Idyryshev; Diana Sviderskaya; Meruyert Kaygusuz (International Journal of Food Properties)
This work investigated the biological efficacy of germinated green buckwheat and its flour (GGBF) as an improver of the quality, storability, and safety of mixed horsemeat and chicken (thighs) patties. The addition of germinated green buckwheat and its flour (GGBF) into the patties improved (p ≤ .05) the protein and fat contents, cooking yield, moisture and fat retention, total phenolic content, and DPPH radical scavenging activity. The addition of GGBF resulted in a lower L* value, whereas the a* and b* values were slightly higher, with the storage time exhibiting a preserving effect of green buckwheat sprouts on the color of a product. Also, the sensory evaluation revealed increases (p < .05) in overall acceptability and juiciness scores. Generally, this study identified the antioxidant and textural improvement potentiality of germinated green buckwheat and its flour, which could pave the way for its use as an extender of the shelf life of the patties.